THE IMPACT OF SOCIAL MEDIA ON ENGLISH PEDAGOGY - Bahromova Umida Ulugʻbek qizi; Zubaydova Nilufar Nematullayevna; Saloxiddinov Manuchehr (Ustozlar uchun, 2025)
In the modern world, social media plays a major role in our daily lives, affecting how we communicate, learn, and interact with one another. It has become a platform for sharing information, opinions, and ideas, and it is used by millions of people worldwide. Over the past few decades, social media has also started influencing education, including English pedagogy, which refers to the methods and strategies used to teach English. In this article, I will explore the ways in which social media impacts the teaching and learning of English, both positively and negatively, and discuss its advantages and challenges in my article.